Global Sea Ice Concentration Climate Data Record v3.0 - Multimission ... : OSI-450-a ... - OSI SAF; EUMETSAT SAF On Ocean And Sea Ice (EUMETSAT SAF on Ocean and Sea Ice, 2022)
Daily averaged fractional ice cover in percentage, processed from passive microwave satellite data (SMMR, SSM/I, and SSMIS) over the polar regions. Sea ice concentration and its uncertainties are calculated from swath observations, and averaged and gridded to the daily fields. This CDR benefited from R&D activities in the ESA CCI projects. This is a Thematic Climate Data Record (TCDR). Besides the Thredds server, mentioned in the resources, another way to access this product is through the FTP server ftp://osisaf.met.no/reprocessed/ice/conc/v3p0 ...